Cover Image, Volume 42, Issue 5. (8th August 2019) - Ding, Qingzhi; Wu, Ricardo A.; Yin, Litao; Zhang, Weiwei; He, Ronghai; Zhang, Ting; Jiang, Hanfei; Luo, Lin; Ma, Haile; Dai, Chunhua
Abstract : The cover image is based on the Original Article Antioxidation and memory protection effects of solid‐state‐fermented rapeseed meal peptides on D‐galactose‐induced memory impairment in aging‐mice by Qingzhi Ding et al., DOI10.1111/jfpe.13145 .